Changes in inter-limb muscle coordination induced by muscle fatigue during pedaling - Sato, T.; Shigetome, S.; Tokuyasu, T. (ISBS Proceedings Archive (Michigan), 2019)
The purpose of this study was to investigate the changes in inter-limb muscle coordination brought about by muscle fatigue during pedaling. Four healthy male road cyclists pedaled for 15 min under a 150 W exercise load and a 90 rpm cadence. First, the surface electromyography (sEMG) of the muscles of both lower limbs was measured along with crank angle. Second, the slope of median frequency of a short-time Fourier transform was used to estimate muscle fatigue. Next, non-negative matrix factorization was applied to the time-frequency components of the sEMG to investigate the inter-limb muscle coordination. The result showed that asymmetrical inter-limb muscle coordination was seen in all subjects regardless of muscle fatigue. Failure to counteract muscle fatigue could be explained by the redistribution patterns of the asymmetrical inter-limb muscle coordination, which is considered a muscle fatigue compensation strategy.